MARKETING STRATEGY IN MACHO BUSINESS IN THE CITY OF MOJOKERTO - Priyo Utomo; Komarun Zaman; Aisyah Darti Megasari; nur aini anisa (Sekolah tinggi ilmu ekonomi pemuda, 2022)
the Marketing Strategy in the Macho Business in Mojokerto City. This type of research uses descriptive qualitative research methods by conducting interviews with the owner. The type of data used is primary data with data collection techniques with documentation, interviews, and observations. The results of the marketing strategy analysis show an increase in total sales from year to year and are used as a reference for the effectiveness of marketing strategies in competition between boba beverage companies. and by doing a marketing strategy for contemporary boba drinks, what you have to do is to build good and intense communication with potential buyers, consumers, or customers. With good interaction, it will certainly increase engagement and can keep consumers from choosing to buy boba beverage products and the number of Boba beverage brands in Indonesia has been eaten by fierce competition between brands. In response to the competition, they also formulated a marketing strategy to highlight their branding. Their common strategy is to use social media and innovate their boba drinks.